Penguatan Kemampuan Bahasa Inggris Anak melalui Program Pelatihan Interaktif di RW 03 Kalibaru, Cilincing, Jakarta Utara - Yosua Mordekhai Hutabarat; Isna Damayanti; Shyavara Aisyah; Fatiha Azka Ghassani; Indrawati Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Program aims to strengthen the basic English language skills of children aged 5-12 in RW 03 Kalibaru, Cilincing, North Jakarta. Initial observations revealed low vocabulary mastery and a lack of confidence in communication among these children. With foreign language literacy rates for primary school-aged children in coastal North Jakarta at only 27.5%, non-formal educational intervention is crucial to support their school learning. As part of a university community service program (KKN), this initiative was carried out over three meetings with 30 children. The method used was Participatory Action Research (PAR), which emphasizes active collaboration between program facilitators and the community. The program's implementation included introducing basic materials such as the alphabet, numbers, colors, and vocabulary related to animals and family members, as well as practicing simple conversations like self-introductions and greetings. The learning methods applied were highly interactive, integrating educational games, songs, visualization, and role-playing. The evaluation, using pre-test and post-test instruments, showed a significant improvement in the participants' understanding. The average initial score increased sharply from 68.5 to 85.7, representing a 17.2-point or approximately 25% increase. This improvement proves the effectiveness of the interactive methods used in strengthening material mastery. Furthermore, the program successfully fostered an inclusive and enjoyable learning environment. A social change was observed in the form of increased self-confidence among the children when using English, a willingness to speak in front of their friends, and positive interactions among participants. Overall, this program not only succeeded in enhancing basic English skills but also fostered social transformation through increased confidence and positive interaction. Although challenges such as varying levels of understanding and limited learning media were encountered.